2019
DOI: 10.1152/ajprenal.00361.2018
|View full text |Cite
|
Sign up to set email alerts
|

NFAT5 regulates renal gene expression in response to angiotensin II through Annexin-A2-mediated posttranscriptional regulation in hypertensive rats

Abstract: The aim was to identify new targets that regulate gene expression at the posttranscriptional level in angiotensin II (ANGII)-mediated hypertension. Heparin affinity chromatography was used to enrich nucleic acid-binding proteins from kidneys of two-kidney, one-clip (2K1C) hypertensive Wistar rats. The experiment was repeated with 14-day ANGII infusion using Alzet osmotic mini pumps, with or without ANGII receptor AT1a inhibition using losartan in the drinking water. Mean arterial pressure increased after 2K1C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…In this work, we demonstrated EphA2–YES1–ANXA2 axis as a novel and important pathway that drives GC cell invasion and metastasis. In this chain of axis, EphA2 interacts with YES1 and phosphorylates YES1 at Tyr426 site that results in YES1 activation, activated YES1 interacts with ANXA2 and phosphorylates ANXA2 at Tyr24 site that induces ANXA2 activation and increases ANXA2 nuclear distribution, leading to activation of the tumor-promoting transcription factors [ 33 , 35 38 ] that promotes GC invasion and metastasis (Fig. 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we demonstrated EphA2–YES1–ANXA2 axis as a novel and important pathway that drives GC cell invasion and metastasis. In this chain of axis, EphA2 interacts with YES1 and phosphorylates YES1 at Tyr426 site that results in YES1 activation, activated YES1 interacts with ANXA2 and phosphorylates ANXA2 at Tyr24 site that induces ANXA2 activation and increases ANXA2 nuclear distribution, leading to activation of the tumor-promoting transcription factors [ 33 , 35 38 ] that promotes GC invasion and metastasis (Fig. 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Renal blood flow, was investigated in the original publication (Mitrou et al, 2015 ), and urine production and glomerular filtration rate have been published previously (Lau et al, 2009 ). However, the comparison to previously known AKI genes showed increased expression of lipocalin‐2 (LCN2), in the AKI field often referred to as neutrophil gelatinase‐associated lipocalin (NGAL), which may indicate early renal tissue injury (Mishra et al, 2003 ) or an epithelial stress response (Fahling et al, 2019 ). It should be noted that LCN2 can also be released from activated neutrophils, although other markers of neutrophil activation were not prominently upregulated, and inflammatory cell numbers were not increased in total.…”
Section: Discussionmentioning
confidence: 99%
“…These events are likely to be regulated by post-translational modifications such as phosphorylation. Indeed, angiotensin II activation of the AT1a receptor stimulates the AnxA2 RNA-binding activity, not by upregulating the expression of AnxA2, but by increasing its phosphorylation [67]. The phosphorylation site(s) were not identified, but we have previously shown that Ser25 phosphorylated and ubiquitinated/sumoylated AnxA2 are enriched in mRNP complexes that are not active in translation [50] AnxA2 is part of mRNP complexes containing c-myc mRNA [11,12,14] and other specific mRNAs translated on cytoskeletonbound polysomes [2,13,49].…”
Section: Annexin A2 Interacts With the Ires Region Of C-myc 5ʹutr Containing Two Pseudo-knots In A Ca 2+ -Dependent Mannermentioning
confidence: 99%